Necesidad de regular el sistema de Remuneraciones del Sector Público de los trabajadores, que permita la efectivización del Principio Constitucional de a igual trabajo igual Remuneración art. 326 de la Constitución - Guaicha Ortega, Christian Javier (2016)
This research topic is made on the issue so that there is inequality regarding the remuneration given under the work of the same characteristics in employees working in the public sector which is a real and current problem in our society. Therefore development of this thesis I have proposed general objectives and make a theoretical, legal and critical study of the need to regulate the system of remuneration of public sector workers, which allows the effectuation of the constitutional principle of "equal work, equal pay Article 326 of the constitution numeral 4 ", which was established through the application of methods and scientific techniques, which in turn led me to obtaining results that allowed that the proposal for reform of law. Also of bibliographic doctrinaire collection, thirty surveys was conducted to people who know the environment that is going to try, plus 3 interview with lawyers in our city, with the data that could be reached, it was concluded that they It must regulate the system of remuneration of public sector workers, which allows the effectuation of the constitutional principle of equal work for equal pay art. 326 of the Constitution numeral 4 which is a problem for our society, and that the competent authorities should take appropriate action to eliminate existing discrimination in the salaries of workers regarding the work of the same characteristics. Field research showed to be a reform of the Labour Code, to ensure through competent body the Ministry of Labor relations control and penalties for these irregularities to ensure the constitutional principle of equal work for equal pay.